2016
DOI: 10.3389/fmars.2016.00127
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Atmospheric Dry Deposition Associated Microbes on the Southeastern Mediterranean Sea Surface Water following an Intense Dust Storm

Abstract: This study explores the potential impacts of microbes deposited into the surface seawater of the southeastern Mediterranean Sea (SEMS) along with atmospheric particles on marine autotrophic and heterotrophic production. We compared in situ changes in autotrophic and heterotrophic microbial abundance and production rates before and during an intense dust storm event in early September 2015. Additionally, we measured the activity of microbes associated with atmospheric dry deposition (also referred to as airborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 70 publications
(104 reference statements)
7
42
0
2
Order By: Relevance
“…In low-nutrient low-chlorophyll (LNLC) marine environments, nutrient and trace metal inputs via atmospheric aerosols are considered important sources of macro and micro nutrients (Duce et al, 1991(Duce et al, , 2008Jickells et al, 2005;Kanakidou et al, 2012), fueling microbial production and influencing the bacterioplankton community structure (Moore et al, 2013;Guieu et al, 2014a;Chien et al, 2016;Rahav et al, 2016a). The Eastern Mediterranean Sea (EMS), located in the so-called dustbelt (Astitha et al, 2012), is considered extremely oligotrophic (reviewed in Siokou-Frangou et al, 2010) and is strongly influenced by natural desert sources that contain some of the highest atmospheric dust (mineral aerosol) concentrations near the Earth's surface (Klingmüller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In low-nutrient low-chlorophyll (LNLC) marine environments, nutrient and trace metal inputs via atmospheric aerosols are considered important sources of macro and micro nutrients (Duce et al, 1991(Duce et al, , 2008Jickells et al, 2005;Kanakidou et al, 2012), fueling microbial production and influencing the bacterioplankton community structure (Moore et al, 2013;Guieu et al, 2014a;Chien et al, 2016;Rahav et al, 2016a). The Eastern Mediterranean Sea (EMS), located in the so-called dustbelt (Astitha et al, 2012), is considered extremely oligotrophic (reviewed in Siokou-Frangou et al, 2010) and is strongly influenced by natural desert sources that contain some of the highest atmospheric dust (mineral aerosol) concentrations near the Earth's surface (Klingmüller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Such inputs are more significant during stratified periods, as they enable new production in a period of generally low autotrophic production (Guieu et al, 2010). In addition to new production, it has been shown that leachable nutrients from atmospheric inputs may enhance N 2 fixation, changes in phytoplankton species composition and carbon sequestration (e.g., Mills et al, 2004;Guo et al, 2012;Moore et al, 2013;Bressac et al, 2014;Guieu et al, 2014b;Rahav et al, 2016a). While a low availability of macronutrients (N, P) and metal micronutrients (e.g., Fe, Co) can limit or colimit phytoplankton growth in the ocean (e.g., Moore et al, 2013), high concentrations of some metals (e.g., Cu or Al) can be toxic to phytoplankton (e.g., Paytan et al, 2009;Jordi et al, 2012;Krom et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphingolipids could also derive from Sphingobacterium and some species of Flavobacterium (e.g., Yabuuchi and Moss, 1982;Yano et al, 1982;Yabuuchi et al, 1983;Dees et al, 1985). This notion is supported by (i) the relatively high abundance of their operational taxonomical units among 16S rRNA gene sequences identified during the Global Ocean Sampling survey of marine bacterioplankton metagenome (Yooseph et al, 2010), and (ii) 16S rDNA clone library analysis of dust rains in the Mediterranean, which can contribute roughly 20 µg DNA m −2 and may thus inoculate EMS surface waters with sphingobacteria and/or their characteristic lipids (Itani and Smith, 2016;Rahav et al, 2016).…”
Section: Hierarchical Clustering Analysis Of Ipl Alkyl Chainsmentioning
confidence: 95%
“…Biogeochemical responses to the addition of SD or A, including plankton community composition and production, pigment concentration, and cycling of macro-nutrients and trace elements, were compared in triplicate to unamended control mesocosms over a period of 8 days (Guo et al, 2016;Herut et al, 2016;Rahav et al, 2016;Tsiola et al, 2016;Tsagaraki et al, under revision, this SI). In addition to these bulk biogeochemical measures of food web dynamics, the diversity of algal and bacterial cell membrane lipids provides a moderate level of taxonomic and physiological information (e.g., Sato, 1992;Guschina and Harwood, 2006;Sohlenkamp and Geiger, 2015) that can be applied to assess organic matter reactivity (Harvey and Macko, 1997;Wakeham et al, 1997), plankton communities in the ocean (e.g., Van Mooy and Fredricks, 2010), and carbon and nutrient fluxes in marine food webs (Dalsgaard et al, 2003;Sebastián et al, 2016).…”
Section: Abstract: Diacylglycerol Lipids Fatty Acids Oligotrophic Fmentioning
confidence: 99%